Wetland-use Change on Ecological Impact: A Topic-based Bibliometric Analysis - Suroto, Suroto; Sundawa, Dadang; Bestari, Prayoga; Wahyu, Wahyu (KnE Social Sciences, 2024)
This study employs a bibliometric approach to analyze the global trends in wetlanduse change research published in the Scopus database between 2003 and 2023. Over 396 articles were examined, revealing a staggering sixfold increase in annual publications and a ninefold surge in citations during this period. The USA dominated global research output, followed by Canada and the UK. Moreover, international collaboration showed remarkable growth. Keyword analysis highlighted “water” as a central theme, appearing amongst the top keywords in various categories. Notably, “constructed wetland biodiversity” emerged as a burgeoning research area. This analysis demonstrates the effectiveness of title, author keyword, and keyword plus approaches for mapping the landscape of wetland research. These findings suggest an increasingly vibrant and collaborative field, with water quality and constructed wetland biodiversity demanding particular attention. Moving forward, addressing critical research gaps in areas like climate change impacts and effective wetland management practices will be crucial for the sustainable future of these vital ecosystems. Keywords: bibliometric analysis, ecological impact, wetland-use